A Factor Analysis of Entrepreneurial Leadership for Private Educational Administrators - Rotbamroe, Bunchakkrawan; Janjamroon, Wichai; Phosirikul, Sukit; Thongkham, Worachai; Songsang, Wiraporn (Rajapark Journal, 2022)
The objectives of this research were to analyze the composition and to study the guidelines for developing entrepreneurial leadership for administrators of private schools. The sample group consisted of 940 private school administrators. The research instruments were questionnaires and interview forms. The data were analyzed using basic statistics and corroborative component analysis. The results showed that the developed entrepreneurial leadership measurement model was consistent with the data. The chi-square value was 105, the degree of freedom was 98, the statistical significance level was 0.27, the parameter estimation error was 0.017, the root index standard of the squared mean of the remainder was 0.027, and the level index. The comparative harmony was 0.99, the non-criterion-based suitability index was 0.99, and the main component had a component weight higher than the 0.70 criterion for all components. Sub-elements and indicators have an element weight above the threshold of 0.30 for all elements and indicators. There are guidelines for developing entrepreneurial leadership for the administrators of private educational institutions, namely: 1) organizing a brainstorming meeting for the educational modeling process; 2) meeting to plan how to do the flowchart in a systematic way and to collaborate with everyone. 3) having sufficient background information to be used to make a decision on problems; 4) seeking the best answer to the situation or problem; and 5) having a thorough study of the data, analyzing, and synthesizing information to use in making accurate and clear decisions.